TRANSLATION AS A SPECIAL TYPE OF SOCIAL COMMUNICATION - Muborakxon Tuychiyeva Bahodir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. This article informs about the features and communication skills of translator. Translation by means of another language must build a speech structure that would have the same emotional and psychological impact on the recipient as the original speech structure, that is, would convey the same information and cause the same reaction, no matter by what means.